BRANDING STRATEGIES AND COMPETITIVE ADVANTAGE OF MICRO AND SMALL COFFEE ENTERPRISES: A QUALITATIVE CASE STUDY OF 360 COFFEE IN INDONESIA - Fashi Septiani; Irsandi (PT. Jurnal Center Indonesia Publisher, 2026)
Branding has emerged as a strategic asset for micro and small enterprises (MSEs) to enhance competitiveness in increasingly saturated markets. This study investigates the role of branding strategies in strengthening the competitive advantage of a micro-scale coffee shop in Indonesia, namely 360 Coffee. Employing a qualitative descriptive approach, data were collected through in-depth interviews, observations, and document analysis involving business owners, employees, and customers. The findings reveal that brand identity consistency, emotional engagement with consumers, product differentiation, and service experience significantly contribute to customer loyalty and market positioning. However, the study also identifies challenges related to limited strategic branding planning, constrained resources, and suboptimal digital branding utilization. These findings support previous studies emphasizing that effective branding enables MSEs to create perceived value beyond functional attributes (Kotler & Keller, 2016; Wijoyo et al., 2021). This research contributes to the literature on small business branding by providing empirical evidence from a local coffee enterprise and offers practical insights for MSE owners seeking sustainable competitive advantage.